Clinical Profile and Outcome of COVID-19 in Children at a Tertiary Hospital, Dhaka - Sultana, Mahbuba; Chowdhury, Sayla; Amin, Abdullah Al (Journal of Bangladesh College of Physicians and Surgeons, 2021)
Background: Since the first detection on 8th March 2020 in Bangladesh, the number of cases is rising alarmingly. The paediatric population is also getting infected in Bangladesh. So far there is no study of COVID in children in this country. Aim: This study reports on clinical profile, laboratory findings and outcomes of COVID-19 children admitted to Combined Military Hospital (CMH), Dhaka. Materials and Methods: In this prospective observational study, RT-PCR confirmed fifty COVID-19 patients aged below twelve years were included. Relevant investigations were done in the Armed Forces Institute of Pathology (AFIP). Data were collected from patients and/or their attendants by a structured questionnaire. Results: Mean age was 59.96±43.24 months, 48% were male and 52% were female. Predominant symptoms were fever (44%), cough (26%), anosmia (26%) and diarrhea (12%). There was neutropenia in 66% and lymphocytosis in 84% of cases. Mean neutrophil and lymphocyte counts were 38±13% and 52.5±13%, respectively. Significantly raised CRP observed in 14% and high serum procalcitonin was in10% of cases. Serum LDH, D-Dimer and ferritin were raised in 80%,34% and 6% of affected children, respectively. The majority (98%) of the children were improved and discharged from the hospital. One child died in this cohort. Conclusion: Fever and cough were the predominant symptoms of COVID-19 affected children in this study. Lymphocytosis and neutropenia were two important laboratory finding. Death in COVID-19 is also not uncommon. J Bangladesh Coll Phys Surg 2021; 39(3): 154-159